2017
DOI: 10.5130/ijcre.v10i1.5202
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to impact: A community knowledge mobilisation evaluation framework

Abstract: A community knowledge mobilisation evaluation frameworkWithin community-based prevention initiatives, there is often a disconnection between research and practice (Waddell 2001). Although extensive effort and substantial resources are invested in the development of community-based interventions, the uptake of these interventions in practice has often been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Alternative approaches to evaluating KMb are available, for example, The Community Knowledge Mobilisation Framework 41 , however, this is more limited than the SIF particularly in terms of considering breadth and mechanisms of change. Impact is a contested term, sometimes conceptualised as a linear process 23 in which impact is directly attributable to generation and dissemination of new knowledge. 42 In the present study, impact was viewed from the wide-ranging lens of the SIF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative approaches to evaluating KMb are available, for example, The Community Knowledge Mobilisation Framework 41 , however, this is more limited than the SIF particularly in terms of considering breadth and mechanisms of change. Impact is a contested term, sometimes conceptualised as a linear process 23 in which impact is directly attributable to generation and dissemination of new knowledge. 42 In the present study, impact was viewed from the wide-ranging lens of the SIF.…”
Section: Discussionmentioning
confidence: 99%
“… 21 22 Effective evaluation of KMb activity is essential to better understand if and how stakeholders across communities use new knowledge and to refine strategies. 23 The Social Impact Framework (SIF), although primarily directed to evaluating co-production, offers a comprehensive and structured approach to understanding and documenting micro-meso-macro levels, processes, impacts and mechanisms of the KMb activity and to map the winding pathway of incremental and often subtle changes which are readily overlooked. 24 Beckett et al 12 provide a worked example of application of the SIF and their suggested questions are used here to guide analysis ( box 1 ):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts are distinguished from outcome assessment and effectiveness evaluation in two ways. First, impacts refer to the extent to which the intervention (partnership) has made a societal difference (Van Tulder et al 2016;Worton et al 2017). Societal audiences, as illustrated in Figure 1, may include students, governments, non-government organisations, industry, academics, citizens, and so on.…”
Section: Component 3: Evaluationmentioning
confidence: 99%
“…However, successful implementation of naturopathic research methodologies, and translation and dissemination of research will require a substantial paradigm shift in which naturopathic practitioners adopt a greater level of responsibility for developing an evidence base for naturopathic medicine. Initiatives to support and evaluate knowledge mobilization 70 within the community of naturopathic medical research, education, and practice may play a key, but yet unexplored role. 71 Researchers in this field have an important leadership role to effectively facilitate this transformation, which will benefit health consumers, naturopathic practitioners, and health care systems they serve.…”
Section: Implications and Future Directionsmentioning
confidence: 99%